Compared gametophytic development of threespecies of Phlebodium (Polypodiaceae, s.str.) - Pérez-García, Blanca; Riba, Ramón; Mendoza, Aniceto; Reyes J., Irma (Revista de Biología Tropical, 1998)
Comparison was made of the gametophytic development of Phlebodium araneosum, P. pseudoaureum and P. decumanum. Spores were collected from several Mexican localities ranging in altitude from 30 to 2300 m and sown on agar with mineral salts. Similarities in germination type and prothallial development were observed. Adult gametophytes are cordate-spatulate to cordate-reniforrn; garnetangia are of the typical type of the cornmon leptosporangiate fems. All three species share similar morphogenetic features of the gametophytes, and these do not l end additional characteristics to support the distinction of Phlebodium from Polypodium, Microgramma and Niphidium, as regard the sexual phase.